Pneumocystis carinii (jirovecii) pneumonia (PCP): the most common opportunistic infection observed in HIV/AIDS cases at the University Malaya Medical Centre, Kuala Lumpur, Malaysia - Ibrahim, Jamaiah; Mahmud, Rohela; Tok, E.L.; Tan, C.L.; Tan, W.H.; Teo, W.S.; Leow, H.F. (SEAMEO Regional Tropical Medicine and Public Health Network, 2012)
This retrospective study was conducted among 59 HIV/AIDS patients with opportunistic infections admitted to the University Malaya Medical Centre between 2000 and 2009. Fifty-five point nine percent of cases were Chinese, 25.4 were Malays, 11.9 were Indians and 6.8 were of unknown ethnic origin. The male:female ratio was 2.9:1 (44 males and 15 females). The highest prevalence (38.9) occurred in the 30-39 year old age group. Men comprised 47.7 and women 53.3; the majority of both were married. The majority of cases were Malaysians (89.8) and the rest (10.2) were immigrants. Most of the patients (18.6) were non-laborers, followed by laborers (11.9), the unemployed (5.1) and housewives (3.4). The most common risk factor was unprotected sexual activity (20.3). The two most common HIV/AIDS related opportunistic infections were Pneumocystis carinii (jirovecii) pneumonia (PCP) (62.7) and toxoplasmosis (28.8). Seventy-two point nine percent of patients had a CD4 count <200 cells/mu l and 5.1 had a CD4 count >500 cells/mu l. Eleven point nine percent of cases died during study period. A low CD4 count had a greater association with opportunistic infections. Most of the patients presented with fever (44.1), cough (42.4) and shortness of breath (28.8). Detection of the etiologic pathogens aids clinicians in choosing appropriate management strategies.